Localised Manufacturing of Solar-Powered Water Purification Systems for Rural Communities in South Africa: A Design Thinking Approach - Bello, K.A.; Maladzhi, R.W. (The South African Journal of Industrial Engineering, 2025)
This paper examines the prospects of localised manufacturing of solar-powered water purification systems to solve water quality scarcity in rural communities in South Africa. The design thinking approach emphasises the importance of community engagement, modular system design, and sustainable partnerships in creating technically, economically, and socially viable solutions. The systems, which use solar technology for water purification, aim to reduce reliance on diesel-powered solutions and to promote environmental sustainability. Prototyping and iterative testing with local input ensure that systems meet specific community needs. The current study highlights challenges such as slow adoption rates, technical maintenance, and socio-economic impacts, and offers recommendations about local capacity building, simplified system designs, and integration with broader community infrastructure. The approach aligns with the United Nations’ Sustainable Development Goals, particularly access to clean water, affordable energy, and sustainable communities. The study presents a model for replicable, community-centred innovation in resource-constrained environments.